RASA PERHATIAN KEPADA SISWA YANG BERPENGARUH PENTING KEPADA PROSES BELAJAR MENGAJAR - Nurul Fadila (UIN Antasari Banjarmasin, 2021)
ABSTRACTThis research was intended to explain the influence of civic education teacher’s affection towards student’s character and student’s learning result at SMA Negeri 10 Batang Hari. In this research, the researcher used descriptive quantitative method. The sample of this research was taken as 10% from 479 the number of students at SMA Perintis 2 Bandar Lampung 2011/2012 and the researcher got 48 students as the sample of this research. The data collecting technique in this research were questionnaires, attitude scales and test. Based on the calculation of data analysis, the result showed that there was positive influence and there was significant between civic education teacher’s affection towards student’s character, the higher of civic education teacher’s affection so the higher of student’s character, e.g. instill a sense of mutual help and respect to the students, as well as the lifestyle of a good teacher could increase the student’s c haracter in their daily lives. And also there was positive influence and there was significant between civic education teacher’s affection towards students’ learning result, the higher influence of civic education teacher’s affection, the higher of student’s learning result, e.g. the affection of the teacher could increase students’ enthusiasm in understanding the question and the task of the material with confidence and the students were active in discussion in whole of class.KEYWORDS: Affection; Student Character; Teacher.ABSTRAKPenelitian ini bertujuan untuk menjelaskan pengaruh kasih sayang guru PKn terhadap karakter siswa dan hasil belajar siswa di SMA Negeri 10 Batang Hari. Dalam penelitian ini, peneliti menggunakan metode deskriptif kuantitatif. Sampel penelitian ini diambil sebanyak 10% dari 479 jumlah siswa di SMA Perintis 2 Bandar Lampung 2011/2012 dan peneliti mendapatkan 48 siswa sebagai sampel penelitian ini. Teknik pengumpulan data dalam penelitian ini adalah angket, skala sikap dan tes. Berdasarkan hasil perhitungan analisis data diperoleh hasil bahwa ada pengaruh positif dan signifikan antara kasih sayang guru pendidikan kewarganegaraan terhadap karakter siswa, semakin tinggi kasih sayang guru pendidikan kewarganegaraan maka semakin tinggi karakter siswa, mis. menanamkan rasa saling membantu dan menghargai siswa, serta gaya hidup guru yang baik dapat meningkatkan karakter siswa dalam kehidupan sehari-hari. Serta ada pengaruh positif dan signifikan antara kasih sayang guru pendidikan kewarganegaraan terhadap hasil belajar siswa, semakin tinggi pengaruh kasih sayang guru pendidikan kewarganegaraan, semakin tinggi hasil belajar siswa, mis. kasih sayang guru dapat meningkatkan semangat siswa dalam memahami soal dan tugas materi dengan percaya diri dan siswa aktif dalam diskusi di seluruh kelas.KATA KUNCI: Kasih Sayang; Karakter Siswa; Guru.